ANALISIS KUAT TEKAN BATU BATA DENGAN ONGGOK SEBAGAI BAHAN PENGGANTI SEKAM PADI - Ngudi Hari Crista; Agus Muldiyanto (Universitas Semarang, 2018)
The most widely used material as a house wall is red brick, which is relatively cheap and safe to weather compared to other materials. Red bricks are usually in the manufacturing process by traditional means and fabrication. In general red bricks require additional materials of rice husk in the process of making. Much of the